2020
DOI: 10.51985/jbumdc2019078
|View full text |Cite
|
Sign up to set email alerts
|

Role of Magnetic Resonance Spectroscopy in Differentiating Neoplastic From Non- Neoplastic Ring Enhancing Brain Lesions Taking Surgical Findings as Gold Standard

Abstract: Objective: To evaluate the diagnostic accuracy of Magnetic Resonance spectroscopy (MRS) in distinguishing neoplastic from non-neoplastic ring enhancing brain lesions taking histopathological findings as gold standard. Study Design and Setting: The cross sectional study was conducted at Radiology department of Jinnah Postgraduate Medical Centre. Methodology: Total 102 patients with ring enhancing lesions detected on MRI brain contrast studies were selected for this study. Cases were referred from Outpatient Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
1
1
Order By: Relevance
“…In the current study, the mean choline/NAA ratio in neoplastic lesions was significantly high compared to the mean ratio in non-neoplastic lesions. Our results contrast with the study done by Jesrani et al [ 14 ]. They revealed histopathological analysis and reported that 43.1% of cases were neoplastic, while 56.9% were non-neoplastic.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the current study, the mean choline/NAA ratio in neoplastic lesions was significantly high compared to the mean ratio in non-neoplastic lesions. Our results contrast with the study done by Jesrani et al [ 14 ]. They revealed histopathological analysis and reported that 43.1% of cases were neoplastic, while 56.9% were non-neoplastic.…”
Section: Discussioncontrasting
confidence: 99%
“…MRI along with MRS is a good diagnostic tool when compared to MRI alone, as it has good sensitivity and specificity. This was comparable with the study conducted by Jesrani et al [ 14 ]. The findings of their study show a sensitivity of 87.5%, specificity of 93.3%, and accuracy of 92.1%.…”
Section: Discussionsupporting
confidence: 93%
“…Increased choline in the peritumoural oedema would greatly increase the confidence of diagnosing a high-grade glioma. Differentiation of tumour from nonneoplastic lesions is possible using NAA/Cho and NAA/Cr ratios, with high choline levels seen in the neoplastic lesions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%